(untitled) (Research, Society and Development, 2021)
In recent decades there has been an undeniable advance in the development of new drugs, which have increased the patient’s quality of life, as well as extended the life expectancy of the world population to which they have reach. However, it should be considered that exogenous substances, at supraphysiological levels, or even within normal levels, can mostly cause with deleterious effects, as is the case of corticosteroids, the focus of the study of this study. Articles from MEDLINE, PubMed, Elsevier, Nature Review were analyzed in order to explore the evolution of iatrogenic Cushing Syndrome (CS), which is related to the chronic use of Glucocorticoides (CG). For this purpose, biochemistry, mechanism of action, pharmacokinetics and metabolic effects of CG were described. The parallel with iatrogenic CS was traced in the description of the clinical diagnosis of the disease, based on the previous history of corticosteroid therapy of the patients, as well as the main techniques recommended for weaning the CG, which are with a lower degree of recurrence of the underlying disease and lower risk of adrenal insufficiency (dysfunctions of the Hypothalamus-Pituitary-Adrenal axis).